Hubungan Persepsi Mahasiswa Tentang Peer Assisted Learning (PAL) Praktikum Anatomi Dengan Hasil Ujian Praktikum Anatomi Fakultas Kedokteran Universitas Lampung - Irvan Miftahul Arif; Rika Lisiswanti; Arif Yudho Prabowo; Merry Indah Sari (CV. Jasa Sukses Abadi, 2020)
Peer Assisted Learning (PAL) is a peer learning method that focuses on students as mentors. The Peer Assisted Learning Method has been used in anatomy study in Faculty of Medicine. Peer assisted learning helps improve student achievement and communication. The purpose of this study is to determine the relationship student perceptions about anatomy practicum PAL with the results of the anatomy lab exam. The design of this study uses the analytic observation method with a cross-sectional approach. The sampling technique in the form of total sampling with a population of 225 respondents, 163 respondents participated in the study, and 59 respondents entered into the exclusion criteria. This study uses primary data in the form of student perceptions assessed by Clinical Teaching Preference Questionnaire (CTPQ) and secondary data in the form of anatomical practicum exam in the block Medical Basic Science 2 (MBS2). The data obtained will be tested with the Spearman test. The results of this study obtained the student perception have median value of 35 while result of examination of anatomy practice have average value of 26. Based on the results the spearman test found that there is no relation between student perception about laboratory anatomy PAL with result of anatomical laboratory examination (p = 0.2) with a very weak correlation (r = 0.09).